Compressive Behavior of Rectangle Short Steel Columns Strengthened with Carbon Fiber Sheets. (2017) - Hidekuma, Yuya; Miyashita, Takeshi; Kobayashi, Akira
Abstract: In recent years, a repair method for corroded steel members by bonding carbon fiber sheets with resin has been applied. However, studies about its behavior under large deformation, such as buckling deformations, are insufficient yet. This paper presents the compressive behavior of rectangle short steel columns strengthened by carbon fiber sheets under axial compression. Some carbon fiber sheets were bonded on the outside of the short steel columns designed in a way that local buckling occurred first. Results showed that the buckling strength of the short steel columns was improved by the carbon fiber sheets.